Perceived Quality of Social Relations and Frequent Drunkenness: A Cross-Sectional Study of Spanish Adolescents. (2nd April 2014) - Kjærulff, Thora M.; Rivera, Francisco; Jiménez-Iglesias, Antonia; Moreno, Carmen
Abstract : Aim: The aim of the study was to examine, for female and male students separately, whether perceived quality of relationships with peers and parents and relations in school predict self-reported frequent drunkenness among Spanish adolescents. Methods: The Spanish data from the Health Behaviour in School-aged Children Study (HBSC) 2010 survey were used including 1177 female and 1126 male students aged between 15 and 16 years. Results: For both genders, students reporting low school satisfaction had increased odds of frequent drunkenness. Among females, low and medium levels of classmate support were associated with decreased odds of frequent drunkenness, whereas low perceived maternal knowledge as well as medium and low satisfaction with the family increased odds of being frequently drunk. The proportion of male students reporting medium satisfaction with friendships had significantly lower odds of frequent drunkenness compared with those with high level of satisfaction with friendships. Conclusion: We found different associations between perceived quality of social relations and frequent drunkenness among male and female students. Results showed that social relations seemed to better predictors of frequent drunkenness among female than male students and that other factors than social relations may contribute to explain excessive alcohol use among Spanish adolescents.